A NUMERICAL METHOD AND A PARALLEL ALGORITHM FOR SOLVING THE PROBLEM OF ELECTROMAGNETIC WAVE DIFFRACTION ON A NON-PLANAR PERFECTLY CONDUCTING SCREEN - A. A. Tsupak (Известия высших учебных заведений. Поволжский регион: Физико-математические науки, 2020)
Background. The purpose of the work is to develop and implement the parallel algorithm for numerical solving the problem of electromagnetic wave diffraction by non-planar perfectly conducting screens. Materials and methods. Vector integro-differential equation of the diffraction problem is considered; basis vector functions on non-planar parameterized screens are introduced; the Galerkin method is used to find approximate solutions of the problem. Results. The Galerkin method is implemented using the MPI interface; computational experiments are performed; efficiency of parallelization of the numerical method is analyzed. Conclusions. The results of numerical tests confirmed the convergence of the Galerkin method and usefulness of using parallel algorithms for solving complex vector scattering problems.